Post 2015: making migration work for sustainable development - Benjamin Schraven; Niels Keijzer; Anna Knoll (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Migration stands among the most politically contentious topics in the United Nations (UN) system. This is shown in the current Millennium Development Goals (MDGs), which reflect an approach to human development that does not involve human mobility. Efforts made to promote discussion on the linkages between migration and development in the UN have – since the turn of the millennium – resulted in two UN High- Level Dialogue sessions, the last of which was held in September 2013. These were supported and informed by accompanying processes convening diplomats, experts and other key stakeholders. Building on these efforts, the most recent UN General Assembly felt that migration should be “adequately considered” in the formulation of a post-2015 agenda on global development. Past policy discussions have, however, narrowed the topic of migration to its more functionalist dimensions. Such a functionalist view would involve a choice for particular non-contentious symptoms of migration (e.g. the cost of sending money overseas) and would fall short of adequately reflecting migration as a key element of sustainable development. Although various options for including migration in a post-2015 framework are on the table – ranging from stand-alone goals to efforts to “mainstream” it throughout the framework – further progress necessitates that migration is reflected in a way that respects the sustainable development orientation that the General Assembly has called for. Therefore, discussions should also pay attention to the following key aspects of migration, which have been overlooked or ignored in past debates. Migrants' rights as well as living and working conditions: Many UN members call for better treatment of migrants, yet fail to ratify and enforce international conventions. Internal migration: A post-2015 agenda should include internal migration, given the importance for sustainable development and the high number of similarities with cross-border migration. Environmental change and migration: Migration should be regarded as an opportunity for adaption – and not as a negative consequence of environmental change. Low-skilled migration: Studies show that facilitating low-skilled migration benefits both the country of origin and destination country. Circular migration: European Union (EU) member states' actions should refrain from restrictive measures that directly undermine the benefits of circular migration. Promoting migration for sustainable development cannot be done with a post-2015 framework alone; it requires transforming global institutions. This would include (1) further discussions at the UN level, (2) considering a subsidiarity principle for migration management, (3) a migration data revolution and (4) more “informed” political debates in UN member states.
Keywords: 330